The immature stages of Polypedilum (Pentapedilum) nodosum (Johannsen) and Polypedilum (Tripodura) masudai (Tokunaga) (Diptera, Chironomidae, Chironominae) - Tang, Hong-Qu; Cranston, Peter S.; Zhao, Jian-Gang; Lok, Chan-Wa; Wong, Kai-Chin; Li, Zhi-Qiang (Zootaxa, 2014)
Based on associated material collected from Macau and Guangxi, the pupae and larvae of Polypedilum (Pentapedilum) nodosum Johannsen and P. (Tripodura) masudai Tokunaga are described completely for the first time. Both species are newly recorded from China. Characters for distinguishing the immature stage of these species from other allied Polypedilum species are noted. The previously recorded Polypedilum (Pentapedilum) ‘K1’ of Cranston (1996) is shown to be P. nodosum. Information is provided on distribution and ecological tolerances.